Two-Dimensional Non-Linear Dynamic Response of a Heap Leach Pad Located in Peru - Perez, Frank (2016)
The current technology of lixiviation process has been widely developed since the last thirty years, becoming this in an efficient method to treat oxidized gold, silver and copper minerals and extract precious metals from small and shallow ore deposits. Important mining operations in regions with a higher seismic activity have the leaching process as their main mineral extraction method. This scenery have generated the necessity for further knowledge in dynamic analysis in order to understand the dynamic response and optimize safely the civil and geotechnical designs of these mining structures. This paper studies a real case of a heap leach facility which the ore stack is composed of quartz-sandstone material.